Folding Clothes Tool Using Arduino Uno Microcontroller And Gear Servo - Irawan, Yuda; Wahyuni, Refni; Fonda, Hendry (Universitas Muhammadiyah Yogyakarta, 2021)
Folding clothes is one of the homework that is often done for housewives, from a survey conducted on 200 housewives in Pekanbaru, the problem is that many housewives choose to fold family clothes by hand, this takes time and the energy to do the job. Based on these problems, the authors designed a microcontroller with a servo motor as a practical medium in folding the clothes applied to the clothes folding tool, where the author uses the Hardware Programming Methodology in order to carry out this research smoothly, the materials needed in this research are Arduino Uno, Gear. Servo, Power Supply, and software components. The result of this research is the creation of an automatic clothes folding device that is useful for simplifying household chores. From the test results, it can be concluded that this tool can fold clothes with a duration of 2 seconds.